Perancangan Aplikasi Sistem Pakar Diagnosis Penyakit Pangkreatitis Menggunakan Metode Certainty Factor Berbasis Web - Gama, Fernando; Lina Mulani, Sartika (CV. Shofanah Media Berkah, 2024)
By utilizing information technology can have a positive impact on the business we build. Information technology must be utilized as well as possible because it can provide the desired benefits. In this study, a case study was taken at the Gabriel Manek Atambua Hospital, which is one of the Regional Hospitals in Atambua District. Speckle. To make it easier for medical staff to make an early diagnosis of pancreatitis and overcome the limitations of doctors' practice schedules. The basic system includes hardware and software to coordinate data collected from sales, product stock checking and reporting. The programming language used in making this application is PHP and MySQL as database storage. The method used in this study is the Certainty Factor Method. The Certainty Factor method is a method that defines a measure of certainty about facts or rules to describe an expert's belief in the problem at hand. The system that is built also performs blackbox functional testing and non-functional testing so that the system can be said to be running well. With this Expert System Application, it can make it easier for medical staff to diagnose pancreatitis early and can overcome the limitations of doctors' practice schedules.